Customer Experience in Digital Banking: The Influence of Convenience, Security, and Usefulness on Customer Satisfaction and Customer Loyalty in Indonesia - Susanto, Stefanus Andrew; Manek, Michael Valensius; Setiawan, Rheo Alfonso; Mustikasari, Faranita (Green Publisher Indonesia, 2023)
The emergence of digital banks in Indonesia, such as Blu by BCA, Bank Jago, Allo Bank, and Bank Neo Commerce has been driven by the positive response from the public and the increasing demand for digital banking services, especially in the Covid-19 pandemic. With the growth of digital banking in Indonesia, it is important to understand the factors that shape customer satisfaction and loyalty. This study aims to examine the influence of customer experience on satisfaction and loyalty in the digital banking industry, with focus in Indonesia (Makassar). Seven hypotheses are proposed to examine these relationships. The study utilizes a sample of digital banking customers through convenience sampling and collects data using electronic questionnaires. Structural equation modelling (PLS) is employed for data analysis, considering validity and reliability measures. The findings reveal that convenience and security significantly influence customer satisfaction, while the influence of usefulness is not supported. Additionally, customer satisfaction is identified as a significant mediator in the relationship between customer experience and loyalty. This study emphasizes the importance of improving convenience and security aspects in digital banking services to enhance customer satisfaction and loyalty. In conclusion, this research provides valuable insights for digital banks in Makassar, Indonesia, to enhance their services and cultivate strong customer relationships. Prioritizing convenience and security, along with understanding the influence of customer satisfaction on loyalty, can drive the success of digital banking firm.